Chinese investments in Africa: Evaluating, how the FOCAC Multilateral Framework contributes to legal cooperation - Fraschia, Lee-Anne Paula (Department of Public Law, 2022)
Chinese investments in Africa, are visible in almost all African Countries. In many ways, one could claim, China's commercial activities in Africa has rebranded its image from a dark and desolate continent to an upcoming economic hub. To compliment these commercial activities, the Forum on China-Africa Cooperation (FOCAC) was established in 2000 and played an instrumental role in enhancing the investment relationship between the two sides. However, this increase of investments, inevitably led to the surge of Africa-China investment disputes. The settlement of these disputes, faces many challenges in domestic and international legal frameworks. Therefore, this paper aims to analyse the FOCAC platform's contributions in settling Africa-China investment disputes. The requirement for an effective dispute settlement mechanism, is also imperative for Africa China economic relations. This could, ensure that the commercial relationship between the two sides, endures continuously and yields ample mutual benefits. According to the African Development Bank Group, Africa has an infrastructure gap of approximately U$D93 billion. Thus, African Countries are reliant on Chinese investments because most of these investments focus on developing roads, railways, bridges, airports amongst others. Infrastructure remains a quintessential component regarding economic stimulation and growth. However, many of these infrastructural investments experiences complexities such as quality control checks, environmental damages, unfair labour practices to name a few. Therefore, it is important to establish a dispute settlement forum, which is affordable, easily accessible, non-bias, fast and reliable inter alia. Moreover, many benefits are attributable to Africa-China investments such as the creation of employment, building of key infrastructures and transfers of skills to name a few.6 Considering that, the FOCAC forum significantly boosted economic developments between the two parties, it is worthwhile to investigate its responses to the overwhelming rates of investment disputes.